Extension in Soil conservation - chand, Bishan (Journal of Soil and Water Conservation, 2022)
Soil conservation schemes in various states have for the last many years been implemented both departmentally through legislation and through extension methods. In Pun- jab, for example, whilc afforestation has almost been done departmentally by closure of areas under section 38 of I.F.A. 1927 and section 5 of Punjab Land Preservation Act 1900, terracing and watbandi works on agricultural fields and Cho training works have been executed through extension method. There is, however no denying the fact that the execution of works through extension has been so to say, a source of headache for the executive staff. The fault does not lie with public alone, it lies with us as well. The public is conservative and does not want to give up old methods. Some of them do not want to submit to reason and sometimes even do not want to hear the extension workers; some of the so called educated people in the villages generally mislead the ignorant masses, try to harass the extension worker and grind their own axe into the bargain. On the other hand if the people arc spiteful and callous and do not want to hear us, we are also to blame for that. We have not tried to dispel their doubts regarding our bonafides and have not madc the public soil conservation minded. Our knowledge is sometimes so meagre that we advocate practices of doubtful outcome. We somctimcs set examples and leave precedents which people do not give up pointing out tauntingly every time we contact them to seek their co-operation.